Law Enforcement Against Cybercrime in Online Activities - Sutardi Sutardi; Lucky Ferdiles (Publikasiku, 2023)
Indonesia, as a country based on law (rechtstaat), is not solely based on mere power (machtstaat), consequently that in the life of society, nation and state it is obligatory to comply with the will that has been regulated based on the applicable laws and regulations. One of the concepts in the theory of the welfare state is that the state has the responsibility to provide maximum health services to its citizens. Based on the provisions of Law Number 36 of 2009 concerning Health, in Article 5 paragraph (1) that; Everyone has the same right in obtaining access to resources in the health sector. One of the health sectors is the hospital which is an important part in the health sector and plays a role in supporting the survival of the community to live a healthy and prosperous life. Hospital medical records are an important component in the implementation of hospital management activities. According to the provisions of the legislation, namely Law Number 29 of 2004 concerning Medical Practice Article 46 paragraphs (1) to (3) and Minister of Health Regulation No. 269 of 2008 concerning Medical Records and Medical Records, made by doctors who are included in the management of their responsibilities which are intended for the condition of the patient. For this reason, medical secrets are the obligation of every doctor to maintain them as required by legislation. The obligation to keep medical secrets concerns things that are obtained through disease examination procedures or by chance, which are carried out by doctors, including those related to the patient's health. The problems that can be raised from this research are; 1. How is the construction of laws and regulations in regulating medical secrets? and, 2. Why does the legality of the disclosure of medical secrets require legal reform through a progressive legal approach? Solving the problem is done through a juridical normative research approach. The results of his research, that medical records are facilities that contain information about patients' illnesses and treatments aimed at maintaining and improving a health service regulated by Law No. 29 of 2004 concerning Medical Practice and Minister of Health Regulation No. 269 of 2008 concerning Medical Records. Legal reform regarding the disclosure of medical secrets through a progressive legal approach, constructively hospitals are obliged to comply with these laws and if violated are threatened with administrative sanctions ranging from verbal warnings, written warnings to license revocation and criminal sanctions